2015
DOI: 10.2340/00015555-1958
|View full text |Cite
|
Sign up to set email alerts
|

Il-31 Does not Correlate to Pruritus Related to Early Stage Cutaneous T-cell Lymphomas but is Involved in Pathogenesis of the Disease

Abstract: Mycosis fungoides (MF) and Sézary syndrome (SS) belong to the group of primary cutaneous T-cell lymphomas (CTCL). Regardless of the stage of the disease, patients with MF and SS can suffer from chronic pruritus. The aim of the study was to investigate the correlation between the interleukin 31 (IL-31) serum level, the degree of pruritus and CTCL severity; and to compare the frequency of IL-31 gene polymorphisms between patients and the control group, and between patients at different stages of the disease. Pru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 55 publications
(84 reference statements)
7
52
3
1
Order By: Relevance
“…However, the pathophysiology of CTCL-related pruritus remains unclear. Patients with CTCL may experience pruritus on skin lesions or uninvolved skin, even before other skin-related symptoms manifest [6, 16, 30]. These observations suggest that a soluble pruritic factor could be generated locally at the diseased skin or elsewhere in the body [16].…”
Section: Mechanisms Of Pruritus In Patients With Ctclmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the pathophysiology of CTCL-related pruritus remains unclear. Patients with CTCL may experience pruritus on skin lesions or uninvolved skin, even before other skin-related symptoms manifest [6, 16, 30]. These observations suggest that a soluble pruritic factor could be generated locally at the diseased skin or elsewhere in the body [16].…”
Section: Mechanisms Of Pruritus In Patients With Ctclmentioning
confidence: 99%
“…These observations suggest that a soluble pruritic factor could be generated locally at the diseased skin or elsewhere in the body [16]. CTCL-related pruritus does not typically respond well to anti-histamine treatments, suggesting that mediators other than histamine may be involved [30, 31]. …”
Section: Mechanisms Of Pruritus In Patients With Ctclmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the correlation of IL-31 to pruritic skin lesions and CTCL, a recent casecontrol study set out to determine if IL-31 serum levels correlated with the presence of itch in CTCL patients. However, a previous study did not find a link between serum levels of IL-31 and itch intensity in patients with early stage CTCL (Malek et al, 2015). A subsequent study found that reducing IL-31 using histone deacetylase inhibitors, prednisone or anti-CCR4 monoclonal antibodies in advanced stage CTCL patients significantly reduced pruritus (Cedeno-Laurent et al, 2015).…”
Section: Interleukin-31's Role In Cutaneous T-cell Lymphoma Itchmentioning
confidence: 93%
“…Recent data demonstrated that prednisone reduces IL-31 expression in malignant T cells and this is correlated to reduced itch in cutaneous T-cell lym phoma (CTCL) patients (34). However, a more recent study (39) failed to find a correlation between IL-31 levels in serum and itch severity in patients with CTCL.…”
Section: Diagnostics and Treatmentmentioning
confidence: 95%